Impact of Intermittent Operation on Lifetime and Performance of a PEM Water Electrolyzer. Issue 8 (1st January 2019) - Weiß, A.; Siebel, A.; Bernt, M.; Shen, T.-H.; Tileli, V.; Gasteiger, H. A.
Abstract : The aim of this study is to provide a better understanding of performance degrading mechanisms occurring when a proton exchange membrane water electrolyzer (PEM-WE) is coupled with renewable energies, where times of operation and idle periods alternate. An accelerated stress test (AST) is proposed, mimicking a fluctuating power supply by operating the electrolyzer cell between high (3 A cm −2 geo ) and low current densities (0.1 A cm −2 geo ), alternating with idle periods during which no current is supplied and the cell rests at open circuit voltage (OCV). Polarization curves, periodically recorded during the OCV-AST, reveal an initial increase in activity (≈50 mV after 10 cycles) followed by a significant decrease in performance during prolonged OCV cycling due to an increasing high frequency resistance (HFR) (≈1.6-fold after 718 cycles). These performance changes can clearly be related to the OCV periods, since they are not observed in a reference experiment where the OCV period is replaced by a potential hold at 1.3 V. The origin of the phenomena, which are responsible for the initial performance gain as well as the subsequent decay are analyzed via detailed electrochemical and physical characterization of the MEAs, and an operating strategy to prevent performance degradation is proposed.